DAMPAK PERUBAHAN PENGGUNAAN LAHAN PERTANIAN TERHADAP SOSIAL EKONOMI PETANI SEKITAR LOKASI PERTAMBANGAN BANYU URIP KECAMATAN GAYAM KABUPATEN BOJONEGORO - Aziz Bahtiar Rifa’i; Fadjar Hari Mardiansjah (TATALOKA, 2018)
This study examines the impact of agricultural land use change into a petroleum mining area to farmers’ socioeconomic conditions around petroleum mining project area in Gayam District of Kabupaten Bojonegoro. The analyses used a mix method, using both quantitative and qualitative approaches. The quantitative approach is used to determine the impact of agricultural land use change on the social and economic aspects with the respondent farmers were supported with a scoring method to determine the condition of socioeconomic vulnerability of farmers, while the qualitative approach carried out through in-depth interviews to some informants who have been affected by the project. The results shows that the presence of the petroleum mining industry has not had a positive impact yet on the farmers’ socioeconomic conditions. By the 700 hectares of agricultural land conversion, the agricultural production capacity of the area tends to decrease, including by the decreasing of the productivity of some agricultural land in a radius of 500 m from the fenceof the mining area as they are affected by the fence’s spotlight. The farmers' income also tends to decrease because of the decreasing of their working hours as the big loss of agricultural land in the area. As a result, many farmers should work outside of the area to search replacement of the arable land. These situations lead to a moderate condition of social and economic vulnerability for the farmers, especially for those who still have sufficient assets to meet the needs of their economic.